A dynamic functional model of diode bridge rectifier for unbalanced input voltage conditions. Issue 3 (10th January 2021) - Deriszadeh, Adel; Karabasoglu, Orkun; Ćalasan, Martin P.; Mehdipour, Farnaz
Abstract: Diode bridge rectifiers are employed in many industrial applications wherein, under practical operating conditions, input voltages can be occasionally or inherently unbalanced. Using the switching function method, this paper proposes a new accurate functional model of the diode bridge rectifier capable of dealing with unbalanced input voltage conditions. To take all degrees of unbalanced conditions into account, this paper introduces uneven commutation intervals phenomenon between diodes occurring under unbalanced voltage conditions and proposes dynamically updating switching functions.